Polyethylene Wear in Retrieved Canine Acetabular Components - Dyce, J.; Tompkins, D.; Bhushan, B.; Olmstead, M. L. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The aim of this pilot study was to define the mechanism and mode of polyethylene wear in acetabular components retrieved from seven dogs following therapeutic total hip replacement. The articular surface of each acetabular component was examined using contact profilometry and scanning electron microscopy (SEM). Peak-tovalley distance (P-V) and arithmetic average surface roughness (Ra) were calculated for each quadrant of the surface. Deformation of the regular profile of the machining lines was the least severe form of surface alteration. Randomly orientated scratches, fine tapered filaments, ripples, and coarse surface shredding were common SEM observations. Gouging of the convex surface of the cup was seen in two cases following failure of the polyethylenecement interface. Wear of the nonarticular acetabular rim suggested neck impingement in one case. P-V and Ra were significantly lower in the craniodorsal zone, compared to the average roughness of the other three quadrants (p < 0.05). Abrasion, adhesion and fatigue were the principal mechanisms of polyethylene wear, and were implicated in the production of polyethylene particulate debris. Meticulous removal of abrasive third bodies at the time of surgery, and correct orientation of the acetabular component, should reduce early and severe wear.Polyethylene wear is inevitable following metal-on-polyethylene total hip replacement. In this study, the nature of polyethylene wear in retrieved canine acetabular components was defined, using contact profilometry and scanning electron microscopy. Abrasion, adhesion and fatigue were the principal mechanisms of wear, and were implicated in the production of polyethylene particulate debris.
Keywords: Polyethylene wear; total hip replacement